2022
DOI: 10.1103/physrevx.12.041010
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Hydrodynamics: A Singulant Perspective

Abstract: As an effective theory, relativistic hydrodynamics is fixed by symmetries up to a set of transport coefficients. A lot of effort has been devoted to explicit calculations of these coefficients. Here we propose a shift in perspective: we deploy bootstrap techniques to rule out theories that are inconsistent with microscopic causality. What remains is a universal convex geometry in the space of transport coefficients, which we call the hydrohedron. The landscape of all consistent theories necessarily lie inside … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 111 publications
0
8
0
Order By: Relevance
“…In particular, the gradient expansion has been shown to diverge for this class of solutions [98]. It was also found that the large order behaviour of the gradient series can be expressed in terms of new degrees of freedom, the singulant fields, which track transient effects [62]. The relevance of these advances to the study of attractors remains an interesting challenge for the future.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, the gradient expansion has been shown to diverge for this class of solutions [98]. It was also found that the large order behaviour of the gradient series can be expressed in terms of new degrees of freedom, the singulant fields, which track transient effects [62]. The relevance of these advances to the study of attractors remains an interesting challenge for the future.…”
Section: Discussionmentioning
confidence: 96%
“…The assumption of ultralocality which has lead to Eq. ( 25) is a useful simplification, but it is not strictly obeyed in SYM, and can be avoided at the level of hydrodynamic models [62].…”
Section: Modeling the Non-hydrodynamic Sectormentioning
confidence: 99%
“…Within a certain class of models (inspired by the gauge/gravity correspondence), the position-space hydrodynamic expansion (in proper time) around the Bjorken flow within the MIS theory was shown to diverge factorially [551]. In contrast, for the same theory Fouriertransformed into the momentum space there is a finite convergence radius limited by the branch point singularity closest to the origin in the complex momentum plane [567][568][569][570][571]. This inspired the formulation of hydrodynamics far from equilibrium via resummation [572].…”
Section: Range Of Applicabilitymentioning
confidence: 99%
“…The more advanced use of transseries, transasymptotic summation and the theory of resurgence is less common in applied mathematics [11][12][13][14][15], although becoming more popular in theoretical physics (see e.g. [16][17][18][19][20][21], as well as [22] and references therein). Here, we apply exponential asymptotics and transseries to locate singularities and zeros of a solution to a second-order ordinary differential equation (ODE) that comes from studying Burgers' equation in a small-time limit, using the method of transasymptotics developed in [23][24][25].…”
Section: Introductionmentioning
confidence: 99%